PROBLEMATIKA SANTRI DALAM TAHFIDZUL QUR’AN DI TPA MULKHLISIN DUSUN I JORONG PINAGA KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Muhammad Zikri; Pendi Hasibuan; Iswantir M; Arifmiboy Arifmiboy (KOLONI, 2022)
This research was conducted using interviews and direct documentation to the place where the TPA was located. The key data sources in this study are the students at the Al-Mukhlisin TPA Dusun I Jorong Pinaga, while the secondary data are the ustadz who teach at the Al-Mukhlisin TPA. And for the data analysis technique, the researcher uses reduction, display and verification. Based on the results of the research that has been carried out, the problems faced by students in memorizing the Qur'an may come from the students themselves and can even come from outside the students themselves, the problems faced such as lazy, bored and others that make targets must be memorized by students to be not fully achieved, therefore the Ustadz who teach provide the best solution so that the problems faced by students are reduced and the targets to be achieved can be fully achieved such as motivating students so that they are not lazy, doing variations of methods so they don't bored, doing muraja'ah so that the memorized verses do not forget and coordinate with parents of students to overcome the problem of not being able to divide time and playing gegdet often. Keywords: problematic. Tahfidzul Qur'an, Solution